Properties and efficiency of catalysts produced by an ION beam processing technology - Bannikov, M. G.; Vasilev, I. P. (НТУ "ХПИ", 2010)
Paper presents the test results and properties of catalysts produced by an ion implantation technique. New catalysts showed the same efficiency with much lower expense of noble metals as compared with the catalysts produce by an impregnation. Also shown, that the ion bombardment did not reduce the specific surface area of the catalyst.

Приведены свойства и результаты испытаний катализаторов, полученных путем ионной имплантации. По сравнению с катализаторами, полученными обычными технологиями, опытные катализаторы показывают те же значения коэффициента нейтрализации при значительно меньшем содержании благородных металлов. Показано, что ионная бомбардировка не уменьшает эффективную поверхность носителей.
Keywords: carbon monoxide; oxides of nitrogen; IBP; catalyst; катализаторы; ионная имплантация; благородные металлы